Translocation of diquat dibromide - Mikulás, J.; Lázár, J.; Kazinczi, G. (International Journal of Horticultural Science, 2005)
The aims of our work were to answer the following questions: 1. Diquat dibromide at different concentrations is a contact or systemic herbicide? 2. if translocation occurs what is the extent and direction of it. 3. by what concentration it is translocated in hydroponics. It has been stated that diquat dibromide at different dilutions (40-5%) had systemic effect in Robinia pseudo-acacia in the fields. Its translocation has been occurred apically first, and later basipetally. The extent of translocation depended on the concentration. In hydroponics diquat dibromide has crytallized on the leaf surface of Galinsoga parvif lora and all concentrations (40-0.078%) proved lethal. Recognition and application of systemic characteristics of diquat dibromide is reported here for the first time. Improvement of application method is in the focus of our future work.